Analisis Yuridis Cyber Crime Pembobolan Dana Nasabah pada Aplikasi Mobile Banking dengan Modus Pembobolan Jalur Undangan Pernikahan Palsu - Angela Gabriela Bupu; Karolus Kopong Medan; Heryanto Amalo (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The purpose of this research is to analyze the juridical cybercrime of breaking into customer funds on mobile banking applications with the mode of breaking into fake wedding invitation lines. This research is an empirical legal research that examines all legal events that have occurred through a case approach. Retrieval is done in two ways, namely interviews and document studies. The data obtained is then presented descriptively qualitative. The results showed that the form of responsibility of the Bank to the victim can be in the form of compensation or refund but if the customer can prove that the money was lost due to the fault of the Bank. The countermeasures taken by the Bank are strengthening the mobile banking security system while the efforts of the NTT Regional Police are conducting socialization, cyber patrols, and making preventive and repressive efforts. The obstacles experienced by the NTT Regional Police are the lack of government supervision in the use of the internet, aspects of evidence, and jurisdiction, as well as the lack of public knowledge of cyber crime. Therefore, suggestions for the results of this study are Suggestions that researchers can put forward are the need for special provisions that explicitly regulate mobile banking. The government should provide legal certainty to create a clean and safe social media environment.